Measurement of the W boson polarization in top decay at CDF at √s = 1.8 TeV - Acosta, D; Affolder, T; Albrow, MG; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Ashmanskas, W; Azfar, F; et al. (2005)
The polarization of the W boson in t →Wb decay is unambiguously predicted by the standard model of electroweak interactions and is a powerful test of our understanding of the tbW vertex. We measure this polarization from the invariant mass of the b quark from t → Wb and the lepton from W → lν whose momenta measure the W decay angle and direction of motion, respectively. In this paper we present a measurement of the decay rate (f V+A) of the W produced from the decay of the top quark in the hypothesis of V + A structure of the tWb vertex. We find no evidence for the nonstandard V + A vertex and set a limit on fV+A < 0.80 at 95% confidence level. By combining this result with a complementary observable in the same data, we assign a limit on fv+A < 0.61 at 95% CL. This corresponds to a constraint on the right-handed helicity component of the W polarization of f+ < 0.18 at 95% CL. This limit is the first significant direct constraint on fV+A in top decay. © 2005 The American Physical Society.